2015
DOI: 10.1111/famp.12190
|View full text |Cite
|
Sign up to set email alerts
|

A Balancing Act: Integrating Evidence‐Based Knowledge and Cultural Relevance in a Program of Prevention Parenting Research with Latino/a Immigrants

Abstract: Family therapists have a unique opportunity to contribute toward the reduction of widespread mental health disparities impacting diverse populations by developing applied lines of research focused on cultural adaptation. For example, although evidence‐based prevention parent training (PT) interventions have been found to be efficacious with various Euro‐American populations, there is a pressing need to understand which specific components of PT interventions are perceived by ethnic minority parents as having t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
7
36
0
Order By: Relevance
“…For example, the vast majority of parents in our studies were raised in impoverished communities with caregivers exposed to intense poverty, shortage of basic services, including lack of access to mental health services, and parenting prevention programs. Similarly, parents in our studies have consistently reported exposure to various instances of discrimination in the US as low-income immigrants (Parra-Cardona et al, 2016, 2018). …”
Section: Healing Through Parenting: An Integrative and Applied Modelsupporting
confidence: 70%
See 4 more Smart Citations
“…For example, the vast majority of parents in our studies were raised in impoverished communities with caregivers exposed to intense poverty, shortage of basic services, including lack of access to mental health services, and parenting prevention programs. Similarly, parents in our studies have consistently reported exposure to various instances of discrimination in the US as low-income immigrants (Parra-Cardona et al, 2016, 2018). …”
Section: Healing Through Parenting: An Integrative and Applied Modelsupporting
confidence: 70%
“…Based on empirical findings from our studies, we have corroborated the positive impact of overtly addressing core attachment principles with parents (Parra-Cardona et al, 2016, 2018). However, rather than seeking to address in depth caregivers’ issues of insecure attachments with their own parents, our approach has focused on conveying to parents the importance of being the sources of attachment security for their children, as well as the ways in which specific GenerationPMTO parenting skills can promote attachment security (e.g., consistently praising children for good behavior).…”
Section: Healing Through Parenting: An Integrative and Applied Modelsupporting
confidence: 69%
See 3 more Smart Citations